A brief review: The implications of iron supplement for marathon runners on health and performance - Zourdos, M. C.; Sanchez-Gonzalez, M. A.; Mahoney, S. E. (The Journal of Strength and Conditioning Research, 2015)
The marathon is considered one of the most demanding endurance events, imposing an enormous amount of physiological stress on bodily structures, the metabolic machinery, and organ systems. Scientific evidence has conclusively shown that marathoners are in need of special nutritional strategies to maintain performance and health. Indeed, among competitive athletes, marathoners are at greater risk to develop anemia, bone mineral density loss, immunosuppression, and other clinical syndromes that may affect performance. Inadequate dietary intake of the micronutrient iron has been identified as one key factor in the development of the above mentioned anomalies. In fact, iron is one of the few nutrients recommended as a supplement by the American College of Sports Medicine (ACSM), the Academy of Nutrition and Dietetics (AND), and Dietitians of Canada. Therefore, the aim of this review article is to discuss the role of iron on the marathoner's health and performance. Special emphasis will be given to the physiological mechanisms accounting for the additional iron need in this group of athletes and the nutritional strategies intended to counteract iron deficiency